A short introduction to psychoanalysis - Milton, Jane 405193; Polmear, Caroline 461123; Fabricius, Julia 461130 (Los Angeles [i.e. Thousand Oaks, Calif.] ; London : SAGE Publications, 2011)
Includes bibliographical references (p. [191]-203) and index